Removal of toluene in adsorption–discharge plasma systems over a nickel modified SBA-15 catalyst. Issue 106 (1st November 2016) - Xu, Weicheng; Xu, Xiaoxin; Wu, Junliang; Fu, Mingli; Chen, Limin; Wang, Ni; Xiao, Hailin; Chen, Xiaofang; Ye, Daiqi
Abstract : In situ FT-IR spectra show the toluene adsorption process of SBA and Ni–SBA catalysts. Abstract : An atmospheric-pressure dielectric barrier discharge (DBD) has been used to investigate the destruction of low concentrations of toluene with nickel loaded SBA-15 (Ni–SBA) catalyst in adsorption–discharge plasma system. The adsorption capacity and catalytic activity of SBA and Ni–SBA were studied. The experimental results showed that the incorporation of Ni into the ordered hexagonal mesopores of SBA afforded a remarkable enhancement in the catalytic activity and CO2 selectivity. However, the presence of the metal oxide lowered the specific surface area and decreased the adsorbed amount of toluene. In situ FTIR was used to explore catalysts adsorption process, and revealed that incorporation of Ni resulted in partial oxidation of toluene over Ni–SBA. The catalysts, after several adsorption-plasma process cycles, were characterized by XRD and TEM techniques. The results indicated that the plasma treatment tended to decrease the size of the metal oxides and increase their dispersion in the support surface and influence the adsorption and catalytic performance. In addition, GC-MS spectra were used to analyze the by-products and speculate the reason of catalysts deactivation.